(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Environmental issues are still quite serious problems in Indonesia. Deforestation, coral reef damage, air and water pollution, and plastic waste have damaged the natural ecosystem which has an impact on the lives of living things. As a result, natural disasters occur everywhere. This is due to the lack of human awareness of the importance of protecting and preserving nature. The purpose of this study is for humans to have ecological intelligence that is able to foster concern and commitment in protecting, improving and preserving nature. This study was conducted using literature studies and interviews which aimed to determine how ecological intelligence is implemented in the community in the Cirendeu Traditional Village in an effort to preserve the environment. From this study, it was found that local wisdom that is still maintained and implemented by the Cirendeu Traditional Village community has a great influence on ethics and attitudes in behaving towards nature.